2008
DOI: 10.1111/j.1537-2995.2007.01632.x
|View full text |Cite
|
Sign up to set email alerts
|

Possible involvement of heparin-binding protein in transfusion-related acute lung injury

Abstract: HBP appears to be one of the primary effector molecules of antibody-mediated nonhemolytic transfusion reactions including TRALI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 43 publications
2
17
0
Order By: Relevance
“…At this point, no data from patient samples are available that would strengthen the perception of a role of azurocidin in ALI. However, antibodies which are found in TRALI have been shown to trigger discharge of azurocidin from neutrophils (192). In addition, in circumstances that may lead to ALI such as severe burns or sepsis, circulating azurocidin levels are increased significantly, allowing speculation on their potential role in lung damage (193)(194)(195).…”
Section: Neutrophil-derived Cationic Polypeptidesmentioning
confidence: 99%
“…At this point, no data from patient samples are available that would strengthen the perception of a role of azurocidin in ALI. However, antibodies which are found in TRALI have been shown to trigger discharge of azurocidin from neutrophils (192). In addition, in circumstances that may lead to ALI such as severe burns or sepsis, circulating azurocidin levels are increased significantly, allowing speculation on their potential role in lung damage (193)(194)(195).…”
Section: Neutrophil-derived Cationic Polypeptidesmentioning
confidence: 99%
“…In addition, studies have indicated that HBP may play an important role in regulating monocyte accumulation in the lung during acute inflammation [9]. HBP appears to be one of the primary effector molecules of transfusion-related acute lung injury [10]. Considering the effect of HBP on the capillary permeability and its release by activated neutrophils, we investigated the plasma levels of HBP and analyzed its value in patients with ALI/ARDS.…”
Section: Introductionmentioning
confidence: 99%
“…anti‐HNA‐3a or anti‐HLA‐A2) stiffen neutrophils or even agglutinate them so that they cannot pass through the narrow lung capillaries and are trapped in the lung where the neutrophils become pro‐adhesive (increased CD11b expression) (42), secrete proinflammatory mediators [interleukin‐8 (IL‐8)], produce cytotoxic ROS, and release enzymes by degranulation (e.g. elastase, myeloperoxidase, azurocidin, and heparin‐binding protein) which can injure the endothelium (40, 42, 43). In a mouse TRALI model using a monoclonal HLA class I antibody, the occurrence of TRALI was dependent on neutrophils and their Fcγ receptors as well as on platelets and on housing of the mice in a non‐pathogen‐free barrier room (39, 44).…”
Section: Pathophysiology Of Immune Tralimentioning
confidence: 99%